Iridium(III)‐Catalyzed Diarylation/Annulation of Benzoic Acids: Facile Access to Multi‐Aryl Spirobifluorenes as Pure Hydrocarbon Hosts for High‐Performance OLEDs. (19th July 2021) - Luo, Yuanyuan; Liu, Zheng; Yang, Ge; Wang, Tianhong; Bin, Zhengyang; Lan, Jingbo; Wu, Di; You, Jingsong
Abstract: Herein disclosed is the first example of diarylation/annulation of benzoic acids via an iridium catalyst system. This protocol provides a step‐economic and highly efficient pathway to 1‐aryl, 1, 3‐diaryl, 1, 7‐diaryl and 1, 3, 7‐triaryl spirobifluorenes from readily available starting materials. The applications of multi‐aryl spirobifluorenes as pure hydrocarbon (PHC) hosts for red, green, and blue (RGB) phosphorescent organic light‐emitting diodes (PhOLEDs) were explored. Due to high triplet energies, 1, 3‐diaryl spirobifluorenes exhibit the potential as the host material of blue PhOLEDs. 1, 7‐Diaryl spirobifluorene can serve as the host of green PhOLEDs. 1, 3, 7‐Triaryl spirobifluorene is a high‐performance host for red PhOLEDs, which exhibits a high external quantum efficiency (EQE) up to 27.3 %. This work not only exemplifies the great potential of multi‐aryl spirobifluorenes as PHC hosts, but also offers a new approach for the synthesis of these PHC hosts. Abstract : Diarylation/annulation of benzoic acids is accomplished for the first time through an iridium catalyst system. This method streamlines access to a series of novel pure hydrocarbon hosts for phosphorescent OLEDs, which exhibit high external quantum efficiencies up to 27.3 %. This work not only shows the potential of multi‐aryl spirobifluorenes as hosts, but also offers a new synthetic strategy for these hosts.